Social and Economic Costs of Attention-Deficit/Hyperactivity Disorder Across the Lifespan. Issue 1 (January 2022) - Sciberras, Emma; Streatfeild, Jared; Ceccato, Tristan; Pezzullo, Lynne; Scott, James G.; Middeldorp, Christel M.; Hutchins, Paul; Paterson, Roger; Bellgrove, Mark A.; Coghill, David
Objective: To determine the financial and non-financial costs of Attention-Deficit/Hyperactivity Disorder (ADHD) across the lifespan. Method: The population costs of ADHD in Australia were estimated for the financial year 2018 to 2019 using a prevalence approach to cost estimation across all ages. Financial (healthcare, productivity, education and justice systems, and deadweight losses) and non-financial costs were measured (Disability Adjusted Life Years (DALYs)). Results: The total social and economic cost of ADHD in 2018 to 2019 were US12.76 billion (range US8.40 billion to US17.44 billion, with per person costs of US15, 664 per year). Productivity costs made up 81% of the total financial costs, followed by deadweight losses (11%), and health system costs (4%). Loss in terms of wellbeing was significant (US5.31 billion). Conclusion: There is a need to raise public awareness of the considerable socioeconomic impact and burden of ADHD in order to drive investment and policy decisions that improve identification and treatment of ADHD.